Square peg, geomorphic hole: applying geomorphic design principles to established tailings storage facilities - Lee, W; Thomson, H (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
What is geomorphic landform design? Why is it adopted as a closure objective, and how does one apply it to an existing, very square tailings storage facility (TSF)? TSFs are an integral component of mining operations and often represent the most significant and complex challenges in mine closure. Understandably, traditional TSF design prioritises containment and stability over long-term geomorphic considerations. This lends towards conventional facilities that are geometrically shaped, with flat tops, homogenous side slopes and little sympathy for natural analogues. A typical Western Australian TSF is a polygonal paddock-style facility, with the containment of tailings provided by a perimeter embankment, constructed amidst relatively flat terrain. These unnatural, engineered structures are a stark contrast to the natural surrounds, often leading to potential disconnects at closure. Closure used to be an afterthought in the TSF design, construction and operation process. However, compliance with the Global Industry Standard on Tailings Management (GISTM) requires that mine owners and operators demonstrate the feasibility of safe closure throughout the entire tailings life cycle, with a robust closure design. The International Council on Mining and Metals (ICMM’s) Tailings Management: Good Practice Guide recommends that TSFs are designed with ‘objectives of closure in mind from the outset’, creating facilities that become ‘engineered landforms — structures that mimic natural landforms’ to increase long-term stability and resilience. It is well established that the application of geomorphological design principles can greatly improve the closure outcomes of many mine landforms, including better mitigation of environmental risks, increased resilience to degradation by erosion, improved visual amenity and better revegetation outcomes. However, design can be challenging if an existing landform does not lend itself to the application of such principles during the closure phase. This paper suggests concepts that can be adopted during the early TSF design phase to ultimately reduce the risks, complexity and capital required for the inevitable implementation of closure.
Keywords: geomorphic